The accountability generation: exploring an emerging leadership paradigm for beginning principals. Issue 4 (4th July 2018) - Heffernan, Amanda
ABSTRACT: School leaders in Queensland, Australia, are working in a rapidly shifting policy landscape, expected to work towards system-defined improvement measures involving increasingly higher external accountabilities. This article analyses a group of long-term case studies of the effects of school improvement expectations on principals since the introduction of National Assessment Program – Literacy and Numeracy (NAPLAN) in 2008. Foucauldian theory is used to analyse the influence of performative cultures on a group of Queensland principals. A unique feature of this geographical region is the large proportion of small-school principals, the majority of whom are in the early stages of their teaching careers. Having joined the teaching profession post-NAPLAN, the influence of these accountabilities emerges as a point of difference between them and longer-established principals. The article identifies the emergence of this new leadership paradigm as an area inviting further inquiry within the field of educational leadership research, exploring the influence of rapidly shifting expectations on leadership practices.